Coping strategies among immigrant women who have experienced intimate partner violence in North America: A narrative review. (September 2019) - Ozturk, Burcu; Li, Qingyi; Albright, David L.
Abstract: Intimate partner violence (IPV) is experienced in every society. IPV can cause severe mental, physical, social, and economic consequences for survivors, and impact their interpersonal relationships in their families, communities and broader society. Coping strategies may be utilized to minimize or tolerate the internal and external difficulties of such stressful situations. A significant number of IPV victims are immigrants in the U.S. and Canada. This study explores what is known about these victims' coping strategies to develop a better understanding of existing studies in the literature. We systematically reviewed qualitative studies on immigrant female IPV survivor coping strategies that were published in peer-reviewed journals between the year 2007 and 2017. We sought to answer the question, "What is known about coping strategies utilized by female immigrant survivors' of IPV in the US and Canada?" Eight qualitative studies were reviewed, and the results showed that survivors utilized multiple formal and informal coping strategies. We critically explored and summarized the eight studies to understand how immigrant women utilize coping strategies. Highlights: Multiple formal and informal coping strategies were utilized by immigrant women as IPV survivors. Seeking helps are some of the major forms of informal support for immigrant female IPV survivors. Formal supports apply to calling the police or seeking help from criminal justice systems and hospitals. Compared to formal coping strategies, immigrant women preferred to choose informal coping strategies to seek help. There are similarities among immigrant women while using coping strategies.